Online Dynamic Optimization of Feed Flowrate and Temperature Trajectories in Semi Batch Esterification Reactor - F.S. Rohman, F.S. Rohman; N. Aziz, S. A. Sata (2011)
In semi batch esterification process, an operating feed flowrate and temperature reactor has a significant effect on conversion that determines final product quality.